Carbon and phosphorus linkages in Daphnia growth are determined by growth rate, not species or diet. (25th February 2014) - Hood, James M.; Sterner, Robert W.; Pfrender, Michael
Summary Ecological stoichiometry provides a framework for understanding how fitness relates to acquisition and use of elements. This framework predicts a trade‐off between the ability to grow quickly under good food conditions and to minimize growth depression on low‐phosphorus (P) diets. These traits should both be related in some way to organism P content, a commonly used proxy of P demand. Previous tests using Daphnia species did not consistently support this prediction, whereas comparisons made across genera or higher taxonomic groups did. One explanation could be that body P content measured at one point in time is a poor indicator of P demand for growth over an interval. We measured the rate of both mass and phosphorus gain of seven Daphnia species under contrasting food conditions, including low‐ and high‐P algal diets. Similar to other studies, we found no significant relationship between body P content and maximum growth rate or sensitivity to P limitation. On the other hand, Carbon (C) and P specific growth rates were linearly related (R2 = 0·83) to all treatments and species with a positive intercept and slope less than one. This relationship indicates that rapid growth does require high‐P accrual as predicted by the growth rate hypothesis. These results reveal a fundamental and unexpected relationship between growth and P demand that transcends species and diets. C and P coupling in growth represents an alternative measure of P demand that confirms theoretical predictions concerning maximum growth rate, sensitivity to P limitation and P demand as well as revealing unpredicted linkages between P demand and the degree of stoichiometric homeostasis. The straight line coupling of C and P in growth represents a new framework for understanding C and P linkages that does not assume strict homeostasis, but does allow generalization across species and diets.